Deep‐red‐emitting Ca2ScSbO6:Mn4+ phosphors with a double perovskite structure: Synthesis, characterization and potential in plant growth lighting. Issue 3 (22nd November 2021) - Chen, Zhanglin; Tian, Zhaobo; Zhang, Jie; Li, Fei; Du, Songmo; Cui, Wei; Yuan, Xuanyi; Chen, Kexin; Liu, Guanghua
Abstract: Mn 4+ ‐activated double‐perovskite type Ca2 ScSbO6 (CSS) phosphors were synthesized via a high‐temperature solid‐state reaction. The phase purity and crystal structure of obtained samples were investigated by powder X‐ray diffraction (XRD). The successful incorporation of Mn 4+ ions into CSS lattice was confirmed by the combination of energy‐dispersive X‐ray spectra (EDX) and X‐ray photoelectron spectra (XPS) results. The luminescent properties of the CSS phosphors, including the photoluminescence (PL) and PL excitation (PLE) spectra, commission international de l'clairage (CIE) chromaticity coordinates, fluorescence decay curves, quantum yields and temperature‐dependent PL spectra, were investigated in detail. Under 310‐nm excitation, the optimized CSS:0.3%Mn 4+ phosphor exhibited bright deep‐red emission covering a narrow band from 640 nm to 720 nm, which overlaps with the absorbance of phytochromes. The Racah parameters B, C, and local crystal strength Dq were calculated to be 870, 2703, and 1984 cm –1, respectively. Particularly, the emission intensity of CSS:0.3%Mn 4+ still remained 61.4% at 423 K compared with that at room temperature. Therefore, all these outstanding luminescent properties provided the as‐synthesized phosphors a great potential in plant growth lighting.